Pilot study of an online intervention for young people with a first psychotic episode: Thinkapp. (1st June 2022) - Morales-Pillado, C.; Sanchez-Gutierrez, T.; Barbeito, S.; Mayoral, M.; Arango, C.; Leon, L.; Ibañez, A.; Rico, J.; Calvo, A.
Abstract : Introduction: Online interventions can be a complement to maintain the long-term effectiveness of psychosocial interventions in First Episode Psychosis (FEP) that have already demonstrated their efficacy in the short and medium term (Calvo et al., 2015). Objectives: To test the effectiveness of a mobile app–based intervention (Thinkapp) to improve quality of life, functioning and symptomatology, and reduce days of admission and hospitalizations, in young people with FEP. Methods: Fourteen patients with FEP, aged 14–30, recruited from Gregorio Marañón Hospital, Ramón y Cajal Hospital and AMAFE Foundation in Madrid (Spain) received treatment as usual plus a psychoeducational intervention through a mobile app. Changes in dependent variables over the course of the intervention were assessed by means of a battery of clinical tests at baseline, 3-month and 6-month follow-up using a Wilcoxon test. Results: Of the fourteen patients included, 7 patients completed the 6-month follow-up and 8 completed the 3-month follow-up. There were significant differences in days of admission (p = 0.042) between baseline and 6-month follow-up. No significant results were observed in other clinical variables. Conclusions: The study provides preliminary data potentially related to the reduction of days of admissions. Disclosure: No significant relationships.